Does childhood victimization predict specific adolescent offending? An analysis of generality versus specificity in the victim-offender overlap. (March 2020) - Miley, Lauren N.; Fox, Bryanna; Muniz, Caitlyn N.; Perkins, Robert; DeLisi, Matt
Abstract: Background: A large body of research has examined the relationship between victimization and future offending, with results suggesting that crime victims are at higher risk of future criminal behavior—known as the victim-offender overlap. Prior studies have primarily examined the relationship between general victimization (e.g., violent victimization, sexual abuse, and more) and general offending (e.g., violence, sexual offending, and drug use), and focused on adult populations. Objective: The goal of the present study is to expand on prior literature by examining if specific forms of childhood victimization increase the risk of specific and analogous forms of offending among delinquent youth. Method: Based upon a population of 64, 329 high-risk youth offenders in Florida, this study evaluates the specificity of the overlap among youth who were physically abused, sexually abused, or witnessed illegal substance use at home during childhood to determine if these forms of victimization increased the risk of violence, sexual offending, and drug use, respectively, when assessed in multivariate logistic regression models. Results: Results provide considerable support for specificity in the victim-offender overlap, as hypothesized. Specifically, experiencing physical abuse (OR = 1.55, p  < .001), sexual abuse (OR = 3.58, p < .001) and witnessing household substance abuse (OR = 1.66, p  < .001) in childhood each significantly and substantially increased the risk of analogous criminal behavior in adolescence, even when controlling for other risk factors and forms of victimization. Conclusion: This study provided novel evidence for specificity in the victim-offender overlap, even after controlling for confounding variables. Practical implications for early intervention and crime prevention are discussed, as well as implications for future research. Highlighting the importance of specificity in the victimization and adverse childhood experience (ACE) paradigms.